Perancangan Identitas Visual PT. Samudra Oceaneering - Ucok Charly Hutagalung; Riwinoto Riwinoto (JURNAL INTEGRASI, 2015)
PT. Samudra Oceaneering (PTSO) is a company engaged in Testing Services does not damage or commonly known as NDT (Non Destructive Testing). PT. Samudra Oceaneering standing on November 10, 2005, and started the business in the field of Remotely Operated Vehicles (ROV) and Inspection Services. PTSO is a branch company Oceaneering International. Logo PTSO still use the logo Oceaneering International, which is common so do not describe the division of PTSO itself, therefore the old logo need to be replaced in order to describe the identity of the company. By using the method of designing a logo and related procedural generated in the form of office supplies (letterhead, envelopes, folders, business cards, pens, stamps), uniform equipment, operating supplies, media promotion and working equipment. From the examination of the respondents showed that tinggat kapuasan against the new logo increased by 12.4%, these results indicate that this new logo can replace the old logo.